A novel fibrillin-1 gene missense mutation associated with neonatal Marfan syndrome: a case report and review of the mutation spectrum. Issue 1 (December 2016) - Peng, Qian; Deng, Yan; Yang, Yuan; Liu, Hanmin
Abstract Background Marfan syndrome (MFS) is a heritable disorder of connective tissue resulting from pathogenic variants of the fibrillin-1 gene (FBN1 ). Neonatal Marfan syndrome (nMFS) is rare and the most severe form of MFS, involving rapidly progressive cardiovascular dysfunction leading to death during early childhood. The constant enrichment of the nMFS mutation spectrum is helpful to improve our understanding of genotype–phenotype correlations in the disease. Herein, we report a novel dominant mutation in exon 26 ofFBN1 (c.3331 T > C) in a sporadic case with nMFS. Case presentation An 8-month-old Han Chinese girl presented with the classic nMFS phenotype, including prominent manifestations of bone overgrowth, aortic root dilatation, and multiple cardiac valve dysfunctions. Genetic analysis revealed that she was heterozygous for ade novo FBN1 missense mutation (c.3331 T > C). The mutation leads to the substitution of a highly conserved FBN1 cysteine residue (p.Cys1111Arg), which is likely to severely perturb the FBN1 structure because of an alteration of the disulfide bond pattern in the calcium-binding epidermal growth factor-like (cbEGF) 12 domain. This variant was absent in 208 ethnically matched controls, providing further evidence that it may be causative of nMFS. An analysis of nMFS-associated mutations from the UMD-FBN1 database indicates that thosede novo mutations altering disulfide bonds or Ca2+ binding sites of the cbEGF domains encoded by exons 25–33, and a lack of phenotypic heterogeneity may be associated with an increased risk for nMFS. Conclusion We diagnosed an infant with rare nMFS showing rapidly progressive cardiovascular dysfunction and widely systemic features. As the only causalFBN1 mutation identified in the patient, the missense mutation c.3331 T > C (p.Cys1111Arg) was associated with the severe phenotype of MFS. However, the pathogenicity of the novel mutation needs further confirmation in other patients with nMFS. Our review of the prominent characteristics of nMFS mutations relative to classic or incomplete MFS-related mutations will be helpful for the recognition of novel nMFS- associated variants.